1987
DOI: 10.1002/acp.2350010207
|View full text |Cite
|
Sign up to set email alerts
|

Lay knowledge of eyewitness behaviour: A British survey

Abstract: One of the recent concerns in the study of eyewitness memory is how well lay knowledge, i.e. 'common sense', matches the findings of empirical research. A number of American and Canadian studies, some using questionnaire methodology, have found limitations in lay knowledge of eyewitness behaviour. Further studies have extended this general finding beyond the lay public-who are prospective jurors-to legal professionals such as lawyers and policemen. The present study utilized the Knowledge of Eyewitness Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 13 publications
3
52
1
1
Order By: Relevance
“…Based on some early research findings on observation skills (Ainsworth, 1981; Tickner & Poulton, 1975) and face recognition abilities (Malpass, 1981;Woodhead et al, 1979), authors in the 1980s asserted that the expert opinion should be that police officers are no better as eyewitnesses than civilians (e.g., Deffenbacher & Loftus, 1982; Kassin, Ellsworth, & Smith, 1989;Noon & Hollin, 1987). Despite the fact that more recent evidence has revealed that police officers may actually provide superior incident reports, authors in recent years have simply adopted that assertion from the 1980s (see e.g., Benton et al, 2006; Houston, Hope, Memon, & Read, 2013; Kassin, Tubb, Hosch, & Memon, 2001;Odinot et al, 2015).…”
Section: The Experts' Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on some early research findings on observation skills (Ainsworth, 1981; Tickner & Poulton, 1975) and face recognition abilities (Malpass, 1981;Woodhead et al, 1979), authors in the 1980s asserted that the expert opinion should be that police officers are no better as eyewitnesses than civilians (e.g., Deffenbacher & Loftus, 1982; Kassin, Ellsworth, & Smith, 1989;Noon & Hollin, 1987). Despite the fact that more recent evidence has revealed that police officers may actually provide superior incident reports, authors in recent years have simply adopted that assertion from the 1980s (see e.g., Benton et al, 2006; Houston, Hope, Memon, & Read, 2013; Kassin, Tubb, Hosch, & Memon, 2001;Odinot et al, 2015).…”
Section: The Experts' Opinionmentioning
confidence: 99%
“…In The Netherlands, a distinction between police officers and civilians has even been incorporated in the law: a single statement by a civilian eyewitness is not sufficient to convict, but a single statement by a police officer is. 1 Many people, including jurors and judges, believe that police officers are better eyewitnesses than civilians (e.g., Benton, Ross, Bradshaw, Thomas, & Bradshaw, 2006;Deffenbacher & Loftus, 1982;Noon & Hollin, 1987;Yarmey, 1986;Yarmey & Jones, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings of mock-juror surveys are similar to surveys of legal professionals, as respondents typically demonstrate an understanding of eyewitness testimony that is at odds with research findings (Benton et al, 2006;Brigham & Wolfskeil, 1983;Deffenbacher & Loftus, 1982;McConkey & Roche, 1989;Noon & Hollin, 1987). Mock jurors tend to be insensitive to biased procedures used by law enforcement, such as poorly constructed line-ups, misleading feedback or biased instructions (Shaw, Garcia, & McClure, 1999).…”
Section: Knowledge Base Of Jurors Regarding Eyewitness Testimonymentioning
confidence: 81%
“…Simons and Chabris (2012) found that their respondents claimed these memory myths were truths over 50% of the time. Furthermore, previous experience as a witness does not appear to be related to knowledge of eyewitness issues (Noon & Hollin, 1987). Desmarais and Read (2011) conducted a meta-analysis of 23 experiments that documented the knowledge of the general public about factors that may affect the reliability of eyewitness testimony.…”
Section: Knowledge Base Of Jurors Regarding Eyewitness Testimonymentioning
confidence: 99%
See 1 more Smart Citation